Integration of Renewable Energy Technologies in University Campuses: a Case Study. Issue 1 (January 2021) - Nazipov, Farnush; Tokbolat, Serik; Khussainova, Diana; Mustafa, Mohamad; Almahadin, Aziz
Abstract: Renewable energy technologies are becoming widely integrated into energy generation systems around the world. While the majority of such technologies are integrated at a large scale in the form of wind and solar farms, there is a need for their incorporation into the built environment. A university campus is an ideal place for testing and understanding how renewable energy technologies can be integrated at a building site scale. Nazarbayev University in Nur-Sultan, Kazakhstan, is a research intense institution which is set to lead the sustainability-related research in the region. The campus is populated with a number of technologies such as a passive house, wind turbines, and photovoltaic solar panels of different capacities and configuration. The review of the technologies and assessment of their operation allowed the study to understand the nature of pioneering technologies that can be integrated in the climate conditions of the locality and how such solutions can help to increase the awareness and popularize renewable energy through education and research.